Covalent DNA–Protein Cross-Linking by Phosphoramide Mustard and Nornitrogen Mustard in Human Cells - Arnold Groehler; Peter W. Villalta; Colin Campbell; Natalia Tretyakova (2015)
N,N-Bis-(2-chloroethyl)-phosphorodiamidic acid (phosphoramide mustard, PM) and N,N-bis-(2-chloroethyl)-amine (nornitrogen mustard, NOR) are the two biologically active metabolites of cyclophosphamide, a DNA alkylating drug commonly used to treat lymphomas, breast cancer, certain brain cancers, and autoimmune diseases. PM and NOR are reactive bis-electrophiles capable of cross-linking cellular biomolecules to form covalent DNA-DNA and DNA-protein cross-links (DPCs). In the present work, a mass spectrometry-based proteomics approach was employed to characterize PM- and NOR-mediated DNA-protein cross-linking in human cells. Following treatment of human fibrosarcoma cells (HT1080) with cytotoxic concentrations of PM, over 130 proteins were found to be covalently trapped to DNA, including those involved in transcriptional regulation, RNA splicing/processing, chromatin organization, and protein transport. HPLC-ESI(+)-MS/MS analysis of proteolytic digests of DPC-containing DNA from NOR-treated cells revealed a concentration-dependent formation of N-[2-[cysteinyl]ethyl]-N-[2-(guan-7-yl)ethyl]amine (Cys-NOR-N7G) conjugates, confirming that it cross-links cysteine thiols of proteins to the N7 position of guanines in DNA. Cys-NOR-N7G adduct numbers were higher in NER-deficient xeroderma pigmentosum cells (XPA) as compared with repair proficient cells. Furthermore, both XPA and FANCD2 deficient cells were sensitized to PM treatment as compared to that of wild type cells, suggesting that Fanconi anemia and nucleotide excision repair pathways are involved in the removal of cyclophosphamide-induced DNA damage.